Analytical models for channel potential, drain current, and subthreshold swing of short-channel triple-gate FinFETs - Gu, Enyao (2016)
An analytical model for channel potential, subthreshold drain current, and subthreshold swing of the short-channel fin-shaped field-effect transistor (FinFET) is obtained. The analytical model results are verified against simulations, good agreement is observed. The explicit expressions for drain current and subthreshold swing make the model suitable to be embedded in circuit simulation and design tools.